Analisis Kepuasan Kerja Karyawan Dengan Metode IPA (Importance Performance Analysis) Pada Hotel Familie 2 Kota Metro - Ambawani, Sasi; Febriyanto, Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study aims to determine the level of employee job satisfaction with the IPA (Importance Performance Analysis) method at Hotel Familie 2 Metro City. The type of research used by the author is descriptive quantitative research. The data were obtained from the results of observations, documentation and questionnaire results to 31 respondents from Hotel Familie 2 employees. Data analysis was carried out using Importance Performance Analysis (IPA) techniques. The essence of this concept is the level of importance (expectation) is measured in relation to what the company should do in order to produce products and services that meet expectations. The results showed that the value of employee job satisfaction on the employee satisfaction index was 0.7625 in the range of 51% - 80%. So it can be said that in general the employee satisfaction index at Hotel Familie 2 for the attributes tested is quite satisfied. The aspect that has the greatest contribution in shaping employee job satisfaction at Hotel Familie 2 is Leadership which has an index value of 0.9058 or 90.58 % .